Customs Law Enforcement on Exports and Imports: An Empirical Study in Indonesia - Arkam Musa; Sunardi Purwanda; Muhammad Darwis; Muhammad Sabir; Muhammad Akbar Fhad Syahril (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
Law enforcement in the field of customs is an important element in maintaining the country's fiscal interests and economic sovereignty. This study aims to analyze the effectiveness of customs law enforcement in export and import activities, identify the factors contributing to export–import smuggling, and examine the preventive and repressive measures implemented by customs authorities. This article combines a normative legal approach with empirical support sourced from the Directorate General of Customs and Excise (DJBC) and the Parepare Customs and Excise Supervision and Service Office (KPPBC). The focus of the research includes the effectiveness of customs law enforcement, the factors causing the smuggling of export-import goods, and the preventive and repressive strategies applied. The results of the analysis confirm that although the legal framework is relatively comprehensive, implementation challenges—including limited institutional capacity, extensive territorial waters, and a low culture of compliance—hinder the effectiveness of law enforcement. Recommendations include strengthening human resources, implementing risk management, increasing inter-agency cooperation, and enhancing efforts to recover state losses.